The effect of skills training with a visual reflex device (R.G.L) on the development of attentive control and accuracy of futsal soccer scoring for students - Sadiq, Sadiq Jafar; Sadiq, Sadiq Jafar; Oleiwi, Noora Amer (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was to prepare and design skill exercises on the light reaction device( RGL Knowing the effect of these exercises in developing attention control and scoring accuracy for students in the gymnasium game. These exercises were applied to a sample of students of the third stage of the Department of Physical Education and Sports Sciences at Al Mustansiriya University who represent the research community .This sample was randomly selected by lottery and represented two academic divisions. A total of four study areas. These two divisions were divided one as an experimental group on which the exercises designed on a device were applied( RGL. The second division as a control group on which the methodology followed by the Department of Physical Education in teaching football to halls was applied. The results of (14( students from each group were approved, and the percentage of the sample to the research community was (33, 33%(. The pre-tests were applied to the two groups in the variables of attention control and accuracy Scoring and after the lapse of (10( weeks, which is the duration of the implementation of the educational program at the rate of one educational unit every week, the unit time is (90( minutes, on which the post tests were applied for the same variables and the results of the pre and post tests were statistically treated depending on the statistical bag system( SPSS. The two researchers reached several conclusions, among which was that the exercises designed and designed by the researcher were effective in developing attentive control and the accuracy of scoring for the research sample that was applied to it .They recommended several recommendations, the most important of which is taking the results of this study and making use of them in developing the curriculum for the soccer halls lesson for the students of the department. Physical Education and Sports Sciences for the Faculties of Basic Education